Problematika Kedudukan Dan Kewenangan Otoritas Ibu Kota Nusantara Dalam Konteks Demokrasi Indonesia - Yassir Arafat; Fawaid Fawaid (Jurnal Hukum Positum, 2025)
The relocation of Indonesia’s capital city to East Kalimantan, as regulated by Law No. 3 of 2022, presents major constitutional and democratic challenges. The Nusantara Capital Authority, a non-elective body with a “ministerial-level” status, wields extensive powers in governance, licensing, and investment without a local legislative oversight mechanism such as a regional council (DPRD). This institutional design creates legal ambiguity, concentrates executive power, and risks violating the principles of checks and balances and popular sovereignty enshrined in the 1945 Constitution. Moreover, land acquisition processes in the IKN area reveal weak protection of indigenous rights and disregard for the free, prior, and informed consent (FPIC) principle, resulting in spatial injustice and weakened social legitimacy. Using a normative legal approach that combines statutory, conceptual, and historical analyses, this study concludes that the current institutional model of the Capital Authority is inconsistent with the principles of democratic rule of law and good governance. The study recommends revising the IKN Law to clarify the legal status and limit the authority’s powers, while establishing a local legislative body to ensure accountability, public participation, and protection of indigenous rights. Keywords: Nusantara Capital Authority; Constitutional Democracy; Public Accountability.